1996
DOI: 10.1113/jphysiol.1996.sp021326
|View full text |Cite
|
Sign up to set email alerts
|

The hypothesis of the uniqueness of the oculomotor neural integrator: direct experimental evidence in the cat.

Abstract: 1. As far as horizontal eye movements are concerned, the well-known hypothesis, not yet experimentally proved, of the common neural integrator states that the eye-position signal is generated by a common network, regardless of the type of versional movement. The aim of this study was to evaluate the validity of this hypothesis by checking whether the sensitivity to eye position of the neurones of the nucleus prepositus hypoglossi (NPH) (the main component of the system integrating the different incoming veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Thus, lesions in the PH and /or M V nuclei of cats and monkeys produced simultaneous alterations of integration in the different subsystems tested (Cheron et al, 1986a,b;C annon and Robinson, 1987). Furthermore, Godaux and Cheron (1996) have reported that in alert cats the eye position sensitivity of PH neurons during intersaccadic fixation was equal to that measured during VOR. However, some pharmacological results suggest that at least some of the subsystems may have separate integrators (Godaux and Laune, 1983;Pastor et al, 1994;Yokota et al, 1994).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, lesions in the PH and /or M V nuclei of cats and monkeys produced simultaneous alterations of integration in the different subsystems tested (Cheron et al, 1986a,b;C annon and Robinson, 1987). Furthermore, Godaux and Cheron (1996) have reported that in alert cats the eye position sensitivity of PH neurons during intersaccadic fixation was equal to that measured during VOR. However, some pharmacological results suggest that at least some of the subsystems may have separate integrators (Godaux and Laune, 1983;Pastor et al, 1994;Yokota et al, 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, small permanent lesions of the primate marginal zone caused by ibotenic acid impaired the gaze-holding in the horizontal plane but not the integration of signals from vestibular sources (Kaneko, 1992(Kaneko, , 1997. The lateral location of this area, ϳ2 mm from the midline, may explain why Godaux and Cheron (1996), while exploring an area located 1.2-1.6 mm from the midline, did not record neurons with position sensitivity specific for postsaccadic fixations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result is in accordance with biology: tonic and phasic neurons are also found in different brain nuclei (such as in the oculomotor system). For example, in the paramedian reticular formation, the majority of the neurons related to the control of eye movements are phasic neurons coding an eye velocity signal (excitatory or inhibitory burst neurons, Henn et al 1982) whereas in the prepositus hypoglossi nucleus, a group of tonic neurons encode a pure position-related signal of the eye (Escudero and Delgado-Garcia 1988;Escudero et al 1992;Pastor et al 1994;Godaux and Cheron 1996). The coding of movement parameters of the premotoneuronal cells recorded in the motor cortex of behaving animals (Fetz et al 1989) and in the red nucleus revealed that they exhibit at least a pure tonic, a phasic-tonic, or a pure phasic discharge pattern during a ramp-and-hold movement (Fetz 1992).…”
Section: Tonic and Phasic Hidden Neuronsmentioning
confidence: 99%
“…Horizontal gaze holding is provided by a brainstem horizontal neural velocity-to-position integrator [4,5] located in the nucleus prepositus hypoglossi and the medial vestibular nucleus [3,6]. Robinson proposed that the neural velocity-to-position integrator is inherently "leaky" and as a result requires cerebellar input to calibrate its output precisely in proportion to eye position [5].…”
Section: Introductionmentioning
confidence: 99%